Coronary Artery Disease in Patients with Severe Mental Illness - Brian Tam To; Roman Roy; Narbeh Melikian; Fiona P Gaughran; Kevin O’Gallagher (Interventional Cardiology: Reviews, Research, Resources)
Severe mental illnesses (SMI), such as schizophrenia and bipolar disorder, are associated with a decrease in life expectancy of up to two decades compared with the general population, with cardiovascular disease as the leading cause of death. SMI is associated with increased cardiovascular risk profile and early onset of incident cardiovascular disease. Following an acute coronary syndrome, patients with SMI have a worse prognosis, but are less likely to receive invasive treatment. In this narrative review, the management of coronary artery disease in patients with SMI is discussed, and avenues for future research are highlighted.